Ways to improve the energy efficiency of pumping units of water supply systems taking into account the dynamics of the increase in the cost of electricity - Zablodsky, M.; Surzhyk, V. (Energy and Automation, 2025)
The article is devoted to the urgent problem of increasing the energy efficiency of pumping units of water supply systems of the housing and communal sector. The purpose of the study is to find ways to reduce the electric energy consumption of pumping units by introducing electric motors of an increased energy efficiency class. To achieve the goal, the following tasks were solved: assessment of the technical condition and potential of the total energy consumption of pumping units; assessment of the components of the water supply tariff structure in Ukraine; testing of asynchronous motors of different energy efficiency classes powered by a frequency converter to determine the energy and functional properties; assessment of the level of energy saving of a pumping unit using the example of the introduction of an IE5 class motor. Special test methods were used to determine losses and assess the efficiency of AC motors powered by a converter. Functional dependences of torque and current on the speed of rotation and energy indicators on the load level for asynchronous motors of different energy efficiency classes were established. Two categories of parameters that affect the reliability of pumping units when using asynchronous motors of different energy efficiency classes are determined, namely: maximum torque when regulating the supply voltage frequency; thermal limit curves during overloads. An express assessment of the effectiveness of investments in replacing motors with low energy efficiency is carried out. Ways are proposed to curb the growth of tariffs, among which the most predictable and economically feasible is the implementation of the frequency converter - IE5 class motor - pump system. When replacing an AIR type motor with an IE5 class motor, the expected reduction in electricity costs for a 2.2 kW motor is 15.48% with an investment payback period of 1.1 years. The established patterns can be used within the framework of a comprehensive approach to applying energy-efficient measures and increasing the reliability of the operation of pumping units of water supply systems in the housing and communal sector. Key words: energy efficiency, pumping units, water supply, variable frequency drive, electric motor